Online Tahsin and Affective Engagement: Exploring Emotional and Spiritual Experiences of Islamic Education Students - Syafii, Imam; Sariyani, Sariyani (Universitas Islam Negeri Raden Fatah Palembang, South Sumatra, Indonesia, 2025)
This study explores how students experience emotional and spiritual engagement in Universitas Terbuka’s (UT) online tahsin al-Qur’an (Qur’anic recitation) course. Using a mixed-methods design with a qualitative emphasis, data were collected from 30 undergraduate students of the Islamic Religious Education (PAI) program through a 20-item survey and reflective writing prompts. Quantitative data were analyzed descriptively, while qualitative data underwent six-step thematic analysis. Findings reveal three major themes: (1) enhanced motivation to improve tajwīd and correct recitation errors through compassionate feedback; (2) strengthened spiritual engagement resulting from tutor presence, reflective practices, and communal rituals; and (3) deepened daily interaction with the Qur’an, evidenced by consistent muroja’ah, mindful prayer, and increased voluntary worship. These outcomes indicate that online tahsin can cultivate both technical proficiency and spiritual intimacy when designed with empathy, reflection, and structured mentorship. Theoretically, the study extends Reeve’s affective engagement framework into the domain of digital Islamic pedagogy, while practically offering design principles for spiritually-enriched distance learning. It concludes that online Qur’anic education, when humanized and reflective, can serve not only as a medium of instruction but as a transformative spiritual journey.